2003
DOI: 10.1159/000071824
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of the Degree of Dementia by Means of EEG

Abstract: The aim of the study was to elaborate a method to estimate the degree of cognitive impairment in Alzheimer’s disease from the EEG quantitative indicators. We examined 38 unmedicated patients with a diagnosis of Alzheimer’s disease, with various stages (mild, moderate, and severe) of dementia. The EEG recordings were evaluated both visually and by means of computer analysis. The EEG spectra and coherences in 6 frequency bands were calculated in 16 EEG derivations. Among various EEG indicators, a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 39 publications
5
37
1
1
Order By: Relevance
“…Deficits in working memory are first observed by 7-8 months of age and loss of hippocampal neurons is seen in mice older than 18 months. Such histological, neurological and neurodegenerative changes are also found in human AD brains (29) and attributed to accumulation of A␤. However, 4-month-old AICD transgenic mice show normal APP metabolism, normal A␤ levels and do not accelerate A␤ deposition when crossed to other mouse models of AD.…”
Section: Discussionmentioning
confidence: 70%
“…Deficits in working memory are first observed by 7-8 months of age and loss of hippocampal neurons is seen in mice older than 18 months. Such histological, neurological and neurodegenerative changes are also found in human AD brains (29) and attributed to accumulation of A␤. However, 4-month-old AICD transgenic mice show normal APP metabolism, normal A␤ levels and do not accelerate A␤ deposition when crossed to other mouse models of AD.…”
Section: Discussionmentioning
confidence: 70%
“…Decreased temporo-parietal coherence appeared to be a discriminant variable between AD patients and controls (Jelic et al, 1996). A decrease in alpha coherence and an increase in delta coherence were found to significantly correlate with the degree of dementia (Brunovsky et al, 2003). Lower sychronization likelihood (SL, a method sensitive for both linear and nonlinear synchronization) in the beta band was found to correlate with MMS scores in AD (Stam et al, 2003) and the mean level of sychronization and spontaneous fluctuations in synchronization were found to be lower in AD compared to normal controls in the alpha and beta bands (Stam et al, 2005).…”
Section: Introductionmentioning
confidence: 85%
“…EEG represents a brain imaging tool capable of identifying the earliest signs of brain dysfunction in subjects who go on to decline to mild cognitive impairment or convert to dementia, characterized by increased theta power [29]. Furthermore, previous studies have consistently demonstrated the relationship of increased delta and/ or theta power to the severity and progression of dementia [e.g., [30][31][32][33][34][35][36][37][38]. A prominent decrease in alpha and/or beta power in cognitive decline has also been reported [e.g., [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%